PENGAWASAN KEIMIGRASIAN TERHADAP ORANG ASING DALAM RANGKA PENDEPORTASIAN DITINJAU DARI UNDANG-UNDANG NOMOR 6 TAHUN 2011 TENTANG KEIMIGRASIAN (STUDI DI KANTOR IMIGRASI KELAS I POLONIA MEDAN) - IMAM BAHRI (Universitas Sumatera Utara, 2013)
ABSTRACT The controlling of international human traffic in one country concerning the immigration aspect of a certain country has universal value and specification in each country which should be in line with the value and need of that country. In Indonesia, the controlling of foreigners is performed by the Directorate General of Immigration for central government level, by Law and Human Rights Office for provincial level, and by the head of the Immigration Office for regional/municipal level. The controlling of foreigners is done by asking them to obtain their visas from the Indonesian Consulates and keeping watch over them when they enter the country, while they are staying, and all their activities in Indonesia, until they leave and return to their respective countries. Deportation is one of the immigration aspects in which it is needed to minimize negative impact of their existence and activities during their stay in Indonesia.The condition and provision of Deportation stipulated in Article 13, Paragraph 1 of Law No. 6/2011 gives the authority to the Immigration Officials to reject any foreigner to enter the Indonesian territory. The immigration controlling constitutes controlling foreigner which includes observing and controlling all their activities since they plan to come to the country, their stay in the country until they leave Indonesia as it is stipulated in Article 66, Paragraph 2 of Law No. 6/2011 on Immigration. Keywords : Controlling Foreigners, Immigration, Deportation.